Exact solution of the Bellman equation for a β-discounted reward in a two-armed bandit with switching arms. (1999) - Donchev, Doncho S.
Abstract : We consider the symmetric Poissonian two-armed bandit problem. For the case of switching arms, only one of which creates reward, we solve explicitly the Bellman equation for a β -discounted reward and prove that a myopic policy is optimal.